PENERAPAN KODE ETIK NOTARIS DALAM PEMBUATAN AKTA PEMBAGIAN WARIS NO 31 MENURUT UUJN NO 2 TAHUN 2014 - Yoki Kurniawan; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2018)
Notary is a position or ordinary we call as general officials appointed by the State and work to serve the public interest. Not only that, a notary also in carrying out its duties and authority must comply fully with the prevailing laws and regulations in Indonesia. Each position certainly has an ethics in the profession which is called a code of ethics, as well as a notary who has a code of ethics in his profession. But out there masi no notaries who violate the code of ethics as mentioned in the law, In accordance with the title of the author of the adopted method of research used is the normative research method supported by interviews that are expected to help answer the problems of this study. The authors conducted interviews with the supervisory board, notaries, and legal experts. In this case the notary has been declared guilty by the Regional Supervisory Board (MPD) and will proceed the case to the level of sanction by the Regional Supervisory Board (MPW) and after receiving the sanction it will proceed to the next level of Central Assembly (MPP) to be sanctioned which has been granted by the level of the Regional Supervisory Board (MPW).